Manner of Debtor’s Dispute Under the FDCPA is in Dispute - Laura Atack (Washington University Journal of Law & Policy, 2015)
This Note contemplates the proper mechanism through which a debtor can communicate his or her intention to dispute a debt collection—in writing or orally, pursuant to the Fair Debt Collection Practices Act (FDCPA). The FDCPA was enacted to alleviate problems and abuses associated with debt collection. As the FDCPA pertains to consumer protection, it affords debtors the right to dispute a debt. However, because the FDCPA is not clear on the exact rights of debtors, this Note argues that allowing debtors to orally communicate to debt collectors the wish to dispute a claim comports with the plain language of the FDCPA and is preferable to debtors.
Keywords: Fair Debt Collection Practices Act; FDCPA; debt collection; consumer protection